2007
DOI: 10.1159/000099202
|View full text |Cite
|
Sign up to set email alerts
|

The Chemopreventive Polyphenol Curcumin Prevents Hematogenous Breast Cancer Metastases in Immunodeficient Mice

Abstract: Dissemination of metastatic cells probably occurs long before diagnosis of the primary tumor. Metastasis during early phases of carcinogenesis in high risk patients is therefore a potential prevention target. The plant polyphenol Curcumin has been proposed for dietary prevention of cancer. We therefore examined its effects on the human breast cancer cell line MDA-MB-231 in vitro and in a mouse metastasis model. Curcumin strongly induces apoptosis in MDA-MB-231 cells in correlation with reduced activation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
163
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(170 citation statements)
references
References 67 publications
4
163
1
2
Order By: Relevance
“…[10][11][12] However, despite having been used for thousands of years, its molecular targets have not been very well identified. More recently, Bachmeier et al 13 reported that curcumin significantly decreased the number of lung metastases in (a and B) In the control group, hematoxylin and eosin (h&e) staining showed numerous VM channels (black arrows) formed by tumor cells; red cells are seen at the center of the channels. Double-staining also showed many pas-positive substances lining channels and forming basement membrane-like structures (VM).…”
Section: Resultsmentioning
confidence: 96%
“…[10][11][12] However, despite having been used for thousands of years, its molecular targets have not been very well identified. More recently, Bachmeier et al 13 reported that curcumin significantly decreased the number of lung metastases in (a and B) In the control group, hematoxylin and eosin (h&e) staining showed numerous VM channels (black arrows) formed by tumor cells; red cells are seen at the center of the channels. Double-staining also showed many pas-positive substances lining channels and forming basement membrane-like structures (VM).…”
Section: Resultsmentioning
confidence: 96%
“…Our group [135] evaluated the chemosensitizing effect of curcumin in combination with paclitaxel on breast cancer metastases to the lung. Others examined the effects of curcumin on human breast cancer (MDA-MB-231) cells in an immunodeficient mouse model of metastasis [136] and observed that the number of lung metastases significantly decreased after intercardiac injection of curcumin, a clear demonstration of curcumin's promise for dietary chemoprevention of metastases [136].…”
Section: Curcumin Exhibits Antitumor Activity In Animalsmentioning
confidence: 99%
“…Curcumin (diferuloylmethane) is a major constituent of turmeric powder, which is extracted from the rhizomes of the plant curcuma longa. Many pharmacological and clinical studies support the fact that curcumin has chemopreventive and antiproliferative activity against a variety of human cancers including pancreatic cancers (Ammon and Wahl, 1991;Li et al, 2004;Lev-Ari et al, 2006;Mitra et al, 2006;Reddy et al, 2006;Wang et al, 2006;Aggarwal et al, 2007;Bachmeier et al, 2007;Hauser et al, 2007;Shankar and Srivastava, 2007;Wahl et al, 2007). In addition, curcumin is also pharmacologically safe as it is a naturally occurring compound used as a food-colouring agent and in traditional medicines to treat various diseases in Asian countries (Ammon and Wahl, 1991;Goel et al, 2008).…”
mentioning
confidence: 99%